1993
DOI: 10.1002/art.1780360107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interleukin‐1 on cytokine gene expression in cultured human articular chondrocytes analyzed by messenger rna phenotyping

Abstract: Objective. To investigate the pattern of cytokine gene expression in human articular chondrocytes in culture in response to interleukin-lp (IL-lp). The effect of serum and variations in culture conditions was also studied.Methods. Messenger RNA was extracted from cells, reverse-transcribed to complementary DNA, and amplified by the polymerase chain reaction (PCR), using specific oligonucleotide primers. The PCR products were validated by restriction analysis with specific enzymes and by Southern blot analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Under our experimental conditions, control osteoblast TGFβ 1 mRNA was not sufficient to be quantified, which is in agreement with the results of other authors for normal tissues (Weyand et al 1994). Growth factor mRNAs are not always detectable but are inducible by the stimulus of other growth factors or by varying the culture conditions (Seid et al 1993). In Apert osteoblasts an elevated amount of TGFβ 1 mRNA expression was observed, and this was greater in ASO than in APO.…”
Section: Discussionsupporting
confidence: 92%
“…Under our experimental conditions, control osteoblast TGFβ 1 mRNA was not sufficient to be quantified, which is in agreement with the results of other authors for normal tissues (Weyand et al 1994). Growth factor mRNAs are not always detectable but are inducible by the stimulus of other growth factors or by varying the culture conditions (Seid et al 1993). In Apert osteoblasts an elevated amount of TGFβ 1 mRNA expression was observed, and this was greater in ASO than in APO.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the findings of Pohlers et al (6), we demonstrated increased levels of all markers except TNFα and increased gene expression of VEGF and IL‐6 in synovial membrane. Other investigators have demonstrated up‐regulation of cytokine production in chondrocytes of patients with arthritis (47). In the present study, IGF‐1 protein concentrations were increased in both synovial membrane and cartilage from knees with AIA.…”
Section: Discussionmentioning
confidence: 97%
“…The inducibility of CSFs in chondrocytes has been well studied [8][9][10][11], and the variability found among the human samples may reflect different stages of chondrocyte activation or development. In contrast, TNF-fl, generally known as a lymphotoxin, has not been reported to be found in chondrocytes, but like TNF-a, it is extremely pleiotropic [25].…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes produce an array of cytokines including IL-1 [4], IL-6 [5], IL-8 [6], IL-11 [7], granulocyte colony stimulating factor (G-CSF) [8,9], granulocyte macrophage colony stimulating factor (GM-CSF) [8][9][10], and macrophage colony stimulating factor (M-CSF) [11], some of which are constitutive and may have maintenance functions. Others are inducible and also may be under autocrine control.…”
Section: Introductionmentioning
confidence: 99%